Geropsychological interventions in long-term care - Hyer, Lee, 1944-; Intrieri, Robert (Springer Pub. Co., 2006)
By applying the Selective Optimization with Compensation (SOC) model to various care settings, the editors are able to examine current LTC practices and existing psychosocial issues confronting older LTC patients; either support or challenge them; and offer suggestions and strategies, such as Cognitive Behavior Therapy, for improving the LTC system and residents? physical, psychological, emotional, and social health.